Baznas Reputation Management To Restore Public Trust : (A Case Study on McDonald’s Indonesia’s Donation for Palestine) - Purwakananta, Mohamad Arifin; Patrianti, Tria; Satispi, Evi; Purnamasari, Oktaviana (STEBIS Bina Mandiri, 2025)
Reputation management is a crucial element in maintaining and restoring public trust in philanthropic organizations. This study aims to analyze the reputation management strategies implemented by the National Amil Zakat Agency (BAZNAS) in responding to controversies surrounding donations by McDonald’s Indonesia to Palestine. The research employs a qualitative method with a case study approach. Data were collected through in-depth interviews, document analysis, and participant observation, and analyzed using triangulation to ensure validity. The findings reveal that BAZNAS employed three primary strategies to restore public trust: (1) Transparent Communication, by providing clarifications through mass media and digital platforms to educate the public about the donation fund management mechanisms; (2) Strategic Collaboration, through partnerships with independent parties for audits and evaluations; and (3) Branding Enhancement, through campaigns emphasizing BAZNAS's commitment to humanitarian values and sustainability. These findings indicate that a holistic approach focusing on communication and strengthening institutional values can effectively mitigate negative impacts on an organization's reputation. This study contributes theoretically to the field of reputation management in philanthropic organizations and offers practical implications for similar institutions in addressing trust crises.